The journey before us : first-generation pathways from middle school to college - Nichols, Laura (Critical issues in American education (Rutgers University Press), 2020)
More students are enrolling in college than ever before in U.S. history. Yet, many never graduate. In this book, the author examines why this is by sharing the experiences of aspiring first-generation college students as they move from middle-school to young adulthood. By following the educational trajectories and transitions of Latinx, mainly second-generation immigrant students and analyzing national data, the author explores the different paths that students take and the factors that make a difference. The interconnected role of schools, neighborhoods, policy, employment, advocates, identity, social class, and family reveal what must change to address the "college completion crisis." Appropriate for anyone wanting to understand their own educational journey as well as students, teachers, counselors, school administrators, scholars, and policymakers, this book outlines what is needed so that education can once again be a means of social mobility for those who would be the first in their families to graduate from college.